China, Africa, and the Rest: Recent Trends in Space Science, Technology, and Satellite Development - Julie Klinger (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2020)
Did you know China's first successful contract to build a satellite was for Nigeria's Space Research and Development Agency? Space is booming on the African continent. Millions of dollars in deals to build and launch satellites are being signed with a host of partners. This working paper by Julie Klinger explores how African scientists and entrepreneurs are engaging in space science policy at home and abroad, pushing the frontiers of what is possible in a rapidly transforming political and economic context.
Keywords: 330